Regulatory T Cells Exhibit Distinct Features in Human Breast Cancer - Plitas, George; Konopacki, Catherine; Wu, Kenmin; Bos, Paula D; Morrow, Monica; Putintseva, Ekaterina V; Chudakov, Dmitriy M; Rudensky, Alexander Y (Immunity, 2016)
Regulatory T (Treg) cells reside in lymphoid organs and barrier tissues where they control different types of inflammatory responses. Treg cells are also found in human cancers, and studies in animal models suggest that they contribute to cancer progression. However, properties of human intratumoral Treg cells and those present in corresponding normal tissue remain largely unknown. Here, we analyzed features of Treg cells in untreated human breast carcinomas, normal mammary gland, and peripheral blood. Tumor-resident Treg cells were potently suppressive and their gene-expression pattern resembled that of normal breast tissue, but not of activated peripheral blood Treg cells. Nevertheless, a number of cytokine and chemokine receptor genes, most notably CCR8, were upregulated in tumor-resident Treg cells in comparison to normal tissue-resident ones. Our studies suggest that targeting CCR8 for the depletion of tumor-resident Treg cells might represent a promising immunotherapeutic approach for the treatment of breast cancer.
Keywords: dospělí; nádory prsu; tumor infiltrující lymfocyty; Female; Phenotype; průtoková cytometrie; Adult; mladý dospělý; ženské pohlaví; Lymphocytes, Tumor-Infiltrating; lidé; Flow Cytometry; Breast Neoplasms; receptory CCR8; Aged, 80 and over; stanovení celkové genové exprese; separace buněk; T-Lymphocytes, Regulatory; Aged; Young Adult; Cell Separation; lidé středního věku; transkriptom; senioři nad 80 let; senioři; fenotyp; Transcriptome; regulační T-lymfocyty; Middle Aged; Gene Expression Profiling; Receptors, CCR8; Humans